2016
DOI: 10.1021/acscatal.6b02080
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Conformation of a Hydrogen Bond Mediated Catalyst Enables the Highly Efficient Enantioselective Construction of an All-Carbon Quaternary Stereocenter

Abstract: All reactions were carried out under an atmosphere of argon with magnetic stirring. Solvents were distilled under argon from calcium hydride (CH3CN and CH2Cl2) or sodium/benzophenone (Et2O, THF and toluene). Iridium catalyst Λ-Ir1, 1 pyridylpyrazole L1, 1 bispyrazole L2 2 and the β,β-disubstituted nitroalkene substrates 1,3,4 were prepared according to published procedures. All other reagents were purchased from commercial suppliers (TCI, Aldrich, Alfa and J&K) and used without further purification. Column chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 91 publications
(36 reference statements)
0
28
0
Order By: Relevance
“… 58 In 2016, the same authors reexamined the asymmetric 1,4-addition of indoles to β,β-disubstituted nitroalkenes and increased the efficiency of the catalyst by cyclizing the pendant carboxamide groups into lactams. 59 The resulting reduction in conformational freedom reduced the entropic penalty of hydrogen bonding, and further optimization replaced the pyridylpyrazole ligand with a bispyrazole, rendering the catalyst C 2 -symmetric, with two catalytic sites per iridium complex. Using these optimized ligands, 1,4-additions could be catalyzed with catalyst loadings as low as 0.05 mol % while maintaining high enantioselectivity.…”
Section: Carbon–carbon Bond-forming Reactionsmentioning
confidence: 99%
“… 58 In 2016, the same authors reexamined the asymmetric 1,4-addition of indoles to β,β-disubstituted nitroalkenes and increased the efficiency of the catalyst by cyclizing the pendant carboxamide groups into lactams. 59 The resulting reduction in conformational freedom reduced the entropic penalty of hydrogen bonding, and further optimization replaced the pyridylpyrazole ligand with a bispyrazole, rendering the catalyst C 2 -symmetric, with two catalytic sites per iridium complex. Using these optimized ligands, 1,4-additions could be catalyzed with catalyst loadings as low as 0.05 mol % while maintaining high enantioselectivity.…”
Section: Carbon–carbon Bond-forming Reactionsmentioning
confidence: 99%
“…We recently reported that the related catalyst L-Ir2 is highly effective in the addition of indoles to a-substituted-b-nitroacrylates at catalyst loadings down to 0.05 mol %, which is remarkable for the challenging construction of an all-carbon quaternary stereocenter (Figure 3 c). [23] Although these asymmetric transfer hydrogenation and asymmetric Friedel-Crafts reactions are not new, to the best of our knowledge, the developed metal-templated catalysts outperform all reported organocatalysts and transition-metal catalysts with respect to the combination of turnover number (catalyst loading) and enantioselectivity. However, it is also important to note that one pays a price for these exceptional catalytic properties, namely that the increased structural complexity of the designed catalysts requires tedious multistep syntheses.…”
Section: Angewandte Chemiementioning
confidence: 86%
“…We developed chiral catalysts for transfer hydrogenations, Friedel-Crafts reactions, sulfa-Michael additions, azaHenry reactions, and the a-amination of aldehydes. [19][20][21][22][23] All of these catalysts are based on bis-cyclometalated iridium(III) (Figure 3 b). [22] In this design, the nitroalkene substrate is activated through the formation of two hydrogen bonds to a coordinated amidopyrazole moiety while the Hantzsch ester [24] is activated towards hydride transfer and placed in a suitable position through the formation of a hydrogen bond …”
Section: Metal-templated Organocatalystsmentioning
confidence: 99%
“…Chiral ligands but also chirality at metal exclusively have been exploited to achieve highly stereoselective reactions. [5][6] Nevertheless several exciting examples that make use of octahedral geometries are known in the literature: cobalt [7][8][9][10][11][12] and iridium [13][14][15][16][17][18] have been successfully used to generate octahedral complexes able to perform asymmetric organocatalytic reactions through their coordination sphere. Remarkable examples include those of Gong, Meggers and coworkers, who have disclosed a series of iridium-templated catalysts with exclusive chirality at the metal center that were able to carry out Michael additions and conjugate reductions, aza-Henry reactions, α-amination and Friedel-Craft alkylations in high yields and stereoselectivities.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable examples include those of Gong, Meggers and coworkers, who have disclosed a series of iridium-templated catalysts with exclusive chirality at the metal center that were able to carry out Michael additions and conjugate reductions, aza-Henry reactions, α-amination and Friedel-Craft alkylations in high yields and stereoselectivities. [13][14][15][16][17][18] Catalysis took place through hydrogen bonding interactions from the ligands without any participation of the metal center. In turn, previous work by Belokon and co-workers had made use of Co(III) complexes comprising both chirality at metal and chiral hemisalen ligands to achieve high ee's in the alkylation of enolates under phase transfer conditions or the epoxidation of enones.…”
Section: Introductionmentioning
confidence: 99%